Prison bureaucracies in the United States, Mexico, India, and Honduras - Norris, Brian (Lexington Books, 2018)
Modern prison bureaucracies: monuments of a charitable disposition? -- Poverty among plenty : the need for more knowledge of modern prisons and global public administration -- The origins and structure of prison systems in Mexico and the US -- The origins and structure of prison systems in India and Honduras -- The mis-measure of prison performance -- A tyranny of the educated versus tudors resurgent : prisons in Mexico City and South Carolina -- Differences in bureaucratic performance in two Mexican prisons -- Indian prisons in Delhi and Telangana compared to la Tamara prison in Honduras -- On the meaning of prisons -- Appendix A: Prison staffs -- Appendix B: Messages on prison walls -- Appendix C: Selected prison wards (inmates) -- Appendix D: Security shifts -- Appendix E: Selected interviews -- Glossary -- Bibliography -- Index -- About the author